Parâmetros bioquímicos em jundiás expostos ao zinco - Leitemperger, Jossiele Wesz (2014)
The contamination of the aquatic environment occurs as a consequence of industrial, agricultural and anthropogenic activities. Aquatic ecosystems are often contaminated with metals such as copper and zinc, which are essential in low concentrations but toxic at high concentrations. Thus, the aim of this study was to establish the mean lethal concentration (LC50) within 96 hours of zinc for silver catfish (Rhamdia quelen) and to evaluate the possible effects on biochemical parameters of fish exposed to 0.0 (control), 1.0 and 5.0 mg/L zinc for 96h. The parameters analyzed were reactive substances to thiobarbituric acid (TBARS), protein carbonyl, acetylcholinesterase (AChE), superoxide dismutase (SOD), catalase (CAT), glutathione S-transferase (GST), non-protein thiols (NPSH) and Na+/K+-ATPase. The LC50 value found was 8.07 mg/L. The results of sublethal exposure showed that TBARS levels decreased in liver and brain at every tested Zn concentration. In gills, there was an increase on TBARS levels at 1.0 mg/L and a decrease at 5.0 mg/L, while no changes in muscle were observed. Exposure to zinc decreased protein carbonyls in liver of silver catfish exposed to 5.0 mg/L and gills in every tested concentration. In brain there were no changes in protein carbonyl and in muscle there was an increase at both concentrations. In liver, the SOD activity increased at both zinc concentrations. CAT activity in liver did not change at any concentration. The GST activity decreased in liver and brain increased at both concentrations used. In gills, GST increased in fish exposed to 1.0 mg/L and in muscle at 5.0 mg/L. NPSH levels showed no changes in liver either in gills. In brain there was an increase on NPSH levels at 5.0 mg/L, while the muscle declined at both concentrations. The AChE activity in brain decreased at both zinc concentrations, whereas there was no change in muscle activity for this enzyme. The Na+/K+-ATPase activity was inhibited in gill and intestine in every used concentration. We may conclude that zinc altered biochemical parameters of silver catfish and also the inhibition of brain AChE and Na+/K+-ATPase activity in intestine and gills may be used as biomarkers of waters contaminated by zinc.